A Global Perspective on Quality of Urban Life: A Comparative Analysis of Spatial Quality Criteria - Pelin Keçecioğlu Dağlı; Denanti Nur Iwani (Proceedings of the International Conference of Contemporary Affairs in Architecture and Urbanism-ICCAUA, 2025)
The concept of urban design is a set of planning and design principles that shape the aesthetic quality and physical order of urban spaces. It also ensures that cities are sustainable, effective and livable. The key to creating livable and healthy cities is to determine the principles aimed at increasing the quality of urban space and to make these principles measurable. This study aims to identify the criteria used to evaluate urban spatial quality, examine how these criteria are applied in cities from different countries, and assess the overall quality of urban life. Within the scope of the research, the concept of “Quality of Urban Life” (QoUL) was addressed and QoUL was evaluated in the selected cities. The urban spatial quality criteria were determined based on a literature review and integrated into the evaluation form. At the conclusion of the study, a comparative analysis was conducted between cities in terms of QoUL criteria and a general framework was presented regarding the spatial quality of cities. Ultimately, this research contributes to the development of objective measurement methods for urban quality assessment and offers a guiding framework to enhance the livability of cities.